Surgical treatment of sleep apnea: Association between surgeon/hospital volume with outcomes. (1st July 2013) - Capobianco, Dirce M.; Batilana, Adelia; Gandhi, Mihir; Shah, Jatin; Ferreira, Rodrigo; Carvalho, Elias; Rivero, Thiago S.; Pietrobon, Ricardo; Atallah, Álvaro N.; Prado, Gilmar F.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis To identify the association between surgeon/hospital volume with outcomes in surgical treatment for obstructive sleep apnea (OSA) in a nationally representative sample. We hypothesized that surgeons/hospitals with lower patient volumes would have: higher mortality rates, longer hospital length of stay (LOS), and higher postoperative complication rates and hospitalization charges. Study Design Secondary data analysis of the 2007 Nationwide Inpatient Sample database. Methods We selected 24, 298 adults undergoing OSA surgery. The data analysis included trend test, regression, and multivariate models that were adjusted by demographic and clinical variables. Results The patients were mostly White (76.43%), male (78.26%), with a mean age of 46 years. Patients treated by surgeons with low volume of procedures (1 procedure/year) had significantly higher mortality rate (odds ratio [OR] 3.05; confidence interval [CI], 1.96‐4.77), longer average LOS (increased until 8.16 hours), and higher hospitalization charges (increased up to $1701.75) versus medium‐ and high‐volume surgeons (2–4 procedures/year; greater than/or equal to 5 procedures/year, respectively). Patients treated at hospitals with low volume of procedures (0–5/year) had significantly higher occurrence of oxygen desaturation (OR, 2.12; CI, 1.50–2.99), longer LOS (increased until almost 2 hours) and higher hospitalization charges (at least $951.50 more expensive) versus patients treated at high‐volume hospitals (greater than/or equal to 18 procedures/year). Conclusion Our investigation validates the hypothesis that lower volume standards (surgeon/hospital) are associated with increase of LOS following surgery to treat OSA, as well as lower surgeon volume associated with increase of mortality and hospitalization charges and lower hospital volume with occurrence of oxygen desaturation as postoperative complication. Level of Evidence 2c. Laryngoscope, 124:320–328, 2014